Prevalence of Feeding and Swallowing Disorders in Congenital Heart Disease: A Scoping Review - Norman, Vivienne; Zühlke, Liesl; Murray, Katherine; Morrow, Brenda (Frontiers in Pediatrics, 2022)
Feeding and swallowing difficulties are commonly reported as comorbidities in infants and children with congenital heart disease. These difficulties have negative health consequences for the child and impact the quality of life of both the child and caregivers. This scoping review presents an integrated summary of the published literature on the prevalence of feeding and swallowing difficulties in congenital heart disease. Fifteen peer-reviewed articles, written in English and published in the last 25 years, were included in the review, following a search of relevant databases. The studies reported on a total of 1107 participants across the articles ranging in age from premature infants to children aged 17 years. An overall pooled prevalence of 42.9% feeding and swallowing difficulties was reported, with a prevalence of 32.9% reporting aspiration. A wide prevalence range of feeding and swallowing difficulties was reported across the articles and factors that contributed to this included the ages of participants, and the definition and assessment of feeding and swallowing difficulties used in the studies. The review confirms that feeding and swallowing difficulties are common in infants and children with congenital heart defects, and that assessment and management of these difficulties should be considered part of the standard of care.